Quiet Zone for the patient in an Ambulance: Active Noise Control Technology for Siren Noise Reduction - SHARMA, Manoj Kumar; VIG, Renu; PAL, Ravi; SHANTHARAM, Veena (Archives of Acoustics, 2018)
This paper proposes an active noise control (ANC) application to attenuate siren noise for the patient lying inside ambulance with no sound proofing. From the point of cost effectiveness, a local ANC system based on feedforward scheme is considered. Further, to handle the limitation of limited Zone of Silence (ZoS), the ANC based on virtual sensing is explored. The simulations are done in MATLAB for the recorded ambulance siren noise signal. The results indicate that ANC can be an effective solution for creating a silent environment for the patient.